Some statements for bi-pseudo-integrals and the role on reconstruction of the pseudo-additive measures - Valera, Dhurata (International Journal of Applied Mathematical Research, 2015)
With the support of some very important and special generators, are given some details about the properties of bi-pseudo-integrals and above all, for the first bi-pseudo-integral the relations with integral Lebesgue are listed. Further, will be shown pseudo-linearity of bi-pseudo-integrals and some investigations in reconstructions of pseudo-additive measures by bi-pseudo-integrals synthesized the reciprocal relationship between pseudo-additive measure and bi-pseudo-integral.